2015
DOI: 10.1074/jbc.m115.661272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exogenous Galectin-9 on Human T Cells

Abstract: Background: Signals triggered by galectin-9 in human T cells are poorly understood. Results: Impairment of Lck or T cell receptor-CD3 complex inhibits calcium mobilization and cytokine production but not apoptosis induced by galectin-9. Conclusion: Galectin-9 triggers two independent pathways in T cells, with one mimicking the antigen-specific activation. Significance: We discovered a novel mechanism involved in galectin-9 immunomodulatory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 60 publications
2
38
0
2
Order By: Relevance
“…To confirm their neutralizing activity, we first used the human leukemic T cell line Jurkat, which is known to be responsive to extracellular gal-9 [ 35 , 36 ]. In a previous report, we have shown that in serum-free conditions, Jurkat cells are sensitive to nanomolar concentrations of gal-9 [ 20 ]. We first compared the ability of two isoforms of gal-9 (gal-9S and gal-9M) to induce apoptotic cell death in Jurkat cells by assessing the percentages of annexin-V-positive and propidium iodide-positive (annexin-V + PI + ) cells after 24h of treatment ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm their neutralizing activity, we first used the human leukemic T cell line Jurkat, which is known to be responsive to extracellular gal-9 [ 35 , 36 ]. In a previous report, we have shown that in serum-free conditions, Jurkat cells are sensitive to nanomolar concentrations of gal-9 [ 20 ]. We first compared the ability of two isoforms of gal-9 (gal-9S and gal-9M) to induce apoptotic cell death in Jurkat cells by assessing the percentages of annexin-V-positive and propidium iodide-positive (annexin-V + PI + ) cells after 24h of treatment ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Another known effect of gal-9 on Jurkat cells is the induction of calcium mobilization [ 35 , 38 ]. We previously demonstrated that the rapid calcium mobilization induced by gal-9 in Jurkat cells–which occurs in less than 1 minute—is not required for apoptosis induction [ 20 ]. Thus, we wondered whether our mAbs could neutralize this additional independent effect triggered by extracellular gal-9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Клінічно підтверджена мальабсорбція лакто-зи викликає специфічну деескалацію експресії мРНК галектину-9 (Gal-9) -регулятора тран-спорту глюкози й уратів, основного ліганду для фагоцитарного рецептора Т-клітинного апоптозу Tim-3 (Т-клітинний імуноглобулін і домен 3 му-цину) [11,13].…”
Section: вступunclassified
“…Позаклітинний солютабний Gal-9 проявляє ци-токіноподібний і проапоптичний ефект, пов'язаний з транс-асоціацією з Tim-3-експресуючими кліти-нами [5,11].…”
Section: вступunclassified